GANGGUAN BIOLOGI PADA CROCIDOLOMIA PAVONANA (F.) (LEPIDOPTERA: PYRALIDAE) AKIBAT PERLAKUAN DENGAN EKSTRAK BIJI AGLAIA ODORATISSIMA BLUME (MELIACEAE) - Erwin Cuk Surahmat dan Djoko Prijono . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2002)
Biological interferences in Crocidolomia pavonana (F.) (Lepidoptera: Pyralidae) as affected by the treatment with seed extract of Aglaia odoratissima Blume (Meliaceae). The effects of Aglaia odoratissima seed extract on mortality, feeding, development, and reproduction of Crocidolomia pavonana were studied in laboratory. Ground seeds of A. odoratissima were extracted with methanol, the extract obtained was partitioned in n-hexane and 95% aqueous methanol, and the methanol fraction was partitioned further in chloroform and water. The chloroform fraction obtained was used in all tests. In mortality tests, first- and second-instar larvae C. pavonana were fed with extract-treated broccoli leaf discs. The first instars were also used in the test to determine the effect of the test extract on development and fecundity of C. pavonana, while the second instars were also used in antifeedant test. A. odoratissima extract acted relatively slowly and larval mortality mostly occurred in the instar that was given the feeding treatment. This is also reflected by the relatively small difference between LC50 against second+third instar (0.166%) and that against the second instar only (0.175%). The test extract at all concentrations tested also inhibited feeding by C. pavonana larvae. The test extract at 0.471% delayed the development from the first instar to the pupal stage by 2.57 days compared with control. The treatment with the test extract at 0.095-0.471% decreased the fecundity of the females C. pavonana by 8.6-85.6%. Those various biological interferences in C. pavonana caused by the treatment with A. odoratissima extract can result in substantial suppression of the target pest population in the field.